The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13030568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er on Microstructure and Mechanical Properties of 5052 Aluminum Alloy with Big Width-To-Thickness Ratio

Abstract: The effect of Er on microstructure and mechanical properties of the 5052 aluminum alloy with a big width-to-thickness ratio was investigated by a metallurgical microscope, scanning electron microscope and tensile testing machine. The results showed that the precipitates were slightly refined after Er addition and Al3Fe was transformed into Al6Fe and AlEr with/without a small amount of Fe or Si. The effect of Er on grain refinement was related to its content. When Er content was lower or higher than 0.4%, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Al 5052 is annealed at 345 o C, cooling rate and time at temperature are unimportant. 47 Stress relief is generally not required but can be performed at about 220 o C.…”
Section: Methodsmentioning
confidence: 99%
“…Al 5052 is annealed at 345 o C, cooling rate and time at temperature are unimportant. 47 Stress relief is generally not required but can be performed at about 220 o C.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15][16]. A good amount of works regarding the use of these elements in Al-Mg alloys has been reported [17][18][19][20]. It was found that the modifying action of scandium on cast aluminum is non-uniform.…”
Section: Introductionmentioning
confidence: 99%